Characterization of Emotional Intelligence in Colombian Managers (2015)
Through a quantitative empirical study with a sample of 557 managers from Colombia, the characterization of emotional intelligence (EI) in Colombian managers is established using the Emotional Intelligence Scale of Wong and Law (2002). The study analyses the ability to perceive, appraise and express emotion, own and others, as reflected in the concept of (EI) and its impact on the personal and professional achievements of Colombian managers. The results show that respondents have high capacity to assess and recognize their own emotions, low capacity to assess and understand the emotions of their team members, high capacity for self-control of their emotions in extreme moods, and high capacity to direct their emotions toward achieving competence.